2021
DOI: 10.1097/ccm.0000000000005173
|View full text |Cite
|
Sign up to set email alerts
|

Association Between an Increase in Serum Sodium and In-Hospital Mortality in Critically Ill Patients*

Abstract: OBJECTIVES: In critically ill patients, dysnatremia is common, and in these patients, in-hospital mortality is higher. It remains unknown whether changes of serum sodium after ICU admission affect mortality, especially whether normalization of mild hyponatremia improves survival. DESIGN: Retrospective cohort study. SETTING: Ten Dutch ICUs between January 2011 and April 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…They raised some important points regarding the challenges of observational studies using existing datasets. We agree that our study on the association between an increase of serum sodium during the first 2 days after ICU admission and mortality raises additional questions, for example, on the influence of fluid balance and of administered fluids and medications (2). We have addressed this in the discussion section of our article.…”
supporting
confidence: 54%
“…They raised some important points regarding the challenges of observational studies using existing datasets. We agree that our study on the association between an increase of serum sodium during the first 2 days after ICU admission and mortality raises additional questions, for example, on the influence of fluid balance and of administered fluids and medications (2). We have addressed this in the discussion section of our article.…”
supporting
confidence: 54%
“…Disorders of sodium commonly are encountered in critically ill patients during ICU admission ( 17 ). It is well suggested that sodium metabolism is strictly regulated by the kidney through the interaction of many neurohormonal mechanisms, including the renin-angiotoxin-aldosterone system ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that hypernatremia at the time of hospital admission is highly related to risk of adjusted all-cause mortality within 365 days after discharge for AF patients without HF. Studies have reported that hypernatremia indicates adverse prognosis for the medical patients ( 14 , 33 35 ). Breen et al showed the same result in a cardiac intensive care unit in a retrospective study ( 14 ).…”
Section: Discussionmentioning
confidence: 99%